Feasibility of Jackfruit Leaf Powder Mask For Oily Skin - Nurisma Ayu; Shallu Rahma Savitri; Siska Miga Dewi (International Journal of Multidisciplinary Research of Higher Education, 2023)
The problem of oily facial skin causes a person's lack of confidence. This can cause acne and other facial skin problems. Therefore, researchers chose a jackfruit leaf mask as a solution because it can remove oil from oily skin and get rid of acne. The aim of the research is to determine the feasibility of Jackfruit Leaf Powder masks to be seen in terms of laboratory tests, organoleptic tests and hedonic tests. This research is an experimental study of jackfruit leaf powder masks. Data collection used the documentation and questionnaire methods prepared with a Likert scale consisting of 7 panelists consisting of 2 lecturers, 2 people from beauty clinics, and 3 students. The data collected was processed using a descriptive analysis formula, the percentage of laboratory test results was Flavonoids contained in jackfruit leaf powder masks, namely 1.27%/100 gram sample.